FISHERMAN RESOURCE MANAGEMENT STRATEGY FOR ECONOMIC RECOVERY POST EARTHQUAKE AND TSUNAMI IN DONGGALA DISTRICT,CENTRAL SULAWESI PROVINCE - Darlina, Darlina; Purnamasari, Elly; Ningsih, Etik Sulistiowati; Helminuddin, Helminuddin; Abdusysyahid, Said; Fitriyana, Fitriyana (Jurnal Perikanan Unram, 2025)
The condition of fisheries production in Donggala Regency experienced a significant decline due to the earthquake and tsunami in 2018. After the disaster, the government made various rehabilitation efforts to restore the local economy. The aim of this research is to determine the government and fishermen's strategies in increasing income after the earthquake and tsunami disaster. The method used is qualitative descriptive data analysis. The results of the study show that before the earthquake and tsunami, coastal fishing communities relied entirely on fishing activities at sea to meet their living needs. The average income of fishermen respondents affected by the earthquake and tsunami reached IDR 10,383,775. This figure was obtained from the average receipt of IDR 168,404,125 after deducting the average total costs recorded at IDR 158,020,350. The government's strategy to increase fishermen's income after the earthquake and tsunami includes providing assistance to fishermen, empowering and training fishermen, developing fisheries cultivation, improving infrastructure, increasing market access, and collaborating with international organizations and non-governmental organizations. In addition, the government also focuses on restoring the local economy through micro, small, and medium enterprises (MSMEs) as well as community empowerment and restoring coastal ecosystems. On the other hand, fishermen still choose to focus on fishing efforts as a strategy to increase their income after the disaster